Makna Teologis Kurban dalam Islam dan Hindu: Studi Komparatif atas Simbol Pengorbanan dan Spiritualitas - Sudja, I Komang; Sugyana , Alingga; Jamaluddin, Jamaluddin; Suleyman, Abdul Hamid (Yayasan Albahriah Jamiah Indonesia, 2025)
Studies on sacrifice in Islam and Hinduism generally focus on the ritual aspect, leaving the deeper theological and symbolic dimensions understudied. Furthermore, comparative research systematically examining the meaning of sacrifice based on primary texts from the Quran and Vedic literature is limited, particularly in understanding how both traditions perceive the relationship between humans and God through the symbol of sacrifice. This study aims to describe the theological meaning and symbolism of sacrifice in both religions, analyse theological interpretations and commentaries based on them, and compare the spiritual structures emerging from the texts and ritual practices. A qualitative method employing a comparative theology and symbolic hermeneutics approach is used, with the units of analysis comprising Quranic verses on sacrifice, the concept of yajña in the Rigveda and Upanis ads, and classical Vedantic interpretations and commentaries. Data are analysed through thematic categorisation and exploration of key symbols, such as niyyah, obedience, self-surrender (praṇidhāna), and self-purification. The results of the study indicate that, despite the different forms of ritual—animal slaughter as an expression of obedience and charity in Islam, and yajna as a cosmic offering in Hinduism—both emphasize the subjugation of the ego, awareness of human limitations, an existential orientation to the Transcendent, and the ethical function of sacrifice in shaping moral dispositions and social responsibility. These findings demonstrate the existence of parallel spiritual structures in these two major traditions. The conclusion confirms the research’s contribution to strengthening interfaith dialogue through a shared symbolic framework and opens up space for further studies that integrate community practice data.